2016
DOI: 10.1080/01635581.2016.1180406
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic and Anticarcinogenic Effect ofVicia fabaProtein Hydrolyzates

Abstract: In recent years, the consumption of vegetal-source proteins has been studied to determine their preventing effect on the development of several chronic diseases. The initial purpose of this report was to determine the effect of a hypercholesterolemic diet (HCD) given to mice, alone or with azoxymethane (AOM), on various obesity biochemical biomarkers, as well as on the induction of colon aberrant crypts (aberrant crypt foci; ACF). At the end of the 5-week assay, animals fed the HCD showed alterations in the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 50 publications
(45 reference statements)
1
21
1
2
Order By: Relevance
“…Cette différence entre les deux cinétiques d'hydrolyse pourrait s'expliquer par plusieurs mécanismes, notamment, la spécificité des enzymes vis-à-vis du substrat, l'épuisement des sites accessibles pour l'enzyme, la dénaturation des enzymes et/ou leur inhibition par les produits de l'hydrolyse *17+. Néanmoins, les deux courbes restent typiques aux profils d'hydrolyse des protéines de légumineuses ou celles d'autres végétaux [7,18,19]. Afin de confirmer l'étendue de l'hydrolyse des protéines, une électrophorèse de l'isolat et des hydrolysats de fenugrec, dans des conditions dénaturantes, a été réalisée.…”
Section: Propriété De Piégeage Du Radical Dpphunclassified
“…Cette différence entre les deux cinétiques d'hydrolyse pourrait s'expliquer par plusieurs mécanismes, notamment, la spécificité des enzymes vis-à-vis du substrat, l'épuisement des sites accessibles pour l'enzyme, la dénaturation des enzymes et/ou leur inhibition par les produits de l'hydrolyse *17+. Néanmoins, les deux courbes restent typiques aux profils d'hydrolyse des protéines de légumineuses ou celles d'autres végétaux [7,18,19]. Afin de confirmer l'étendue de l'hydrolyse des protéines, une électrophorèse de l'isolat et des hydrolysats de fenugrec, dans des conditions dénaturantes, a été réalisée.…”
Section: Propriété De Piégeage Du Radical Dpphunclassified
“…Hipocolesterolémico, hepatoprotector, antiinflamatorio, antioxidante, anticáncer, antimicrobiano, antiviral, cardioprotector, neuroprotector, hipotensor, diurético, antinefrítico (Vered et al, 1997;Randhir & Shetty, 2004;Peyvast & Khorsandi, 2007;Fang et al, 2011;Lim, 2012;Boudjou et al, 2013;León-Espinosa et al, 2016). Hurrell et al, 2009Hurrell et al, , 2011.…”
Section: Trébol Blanco Eurasiamentioning
confidence: 99%
“…Faba proteins mainly consist of globulins and represent 24-32% of the faba bean weight. Leon-Espinosa, et al [13] demonstrated the hypocholesterolemic and anti-carcinogenic effect of fava bean protein hydrolysates in a colon cancer mice model. Other faba proteins as favin, a Bowman-Birk type trypsin inhibitor (VFT1-G1), and other peptidic protease inhibitors, have been described to possess anti-proliferative activity toward HepG2 hepatoma cells by inducing chromatin condensation and cell apoptosis [43,44].…”
Section: Fabamentioning
confidence: 99%
“…To assess if BPs are produced naturally during gastrointestinal digestion, in vitro digestions are commonly carried out with proteases (pepsin, trypsin, chymotrypsin, and pancreatin). Researchers have also performed enzymatic hydrolysis with microbial or plant enzymes, such as alcalase, flavourzyme, papain and bromelain, to obtain bioactive sequences [6,[11][12][13][14][15].…”
Section: Soybeansmentioning
confidence: 99%